Validación de un método analítico para la extracción y determinación de enrofloxacina y su metabolito ciprofloxacina en plasma y tejidos de truchas (Oncorhynchus mykiss) - Urzúa, N (Universidad Nacional del Litoral, 2022)
A new pre-treatment and validation of an analytical technique was applied to determine enrofloxacin and ciprofloxacin in plasma and trout tissues. Pre-treatment consisted in adding 300 μL or mg of plasma or target tissue to 300 μL of 50% trichloroacetic acid and homogenizing for 5 minutes, then keeping the samples for 12 hours at 4 °C, centrifuged 30 minutes at 13,500 rpm. Regardless of the matrix analyzed, 150 μL of the supernatant were recovered and 150 μL of known concentrations of enrofloxacin or ciprofloxacin, marbofloxacin as internal standard and 600 μL of methanol were added. Finally, the samples were centrifuged for 15 minutes at 13,500 rpm, and 100 μL of the supernatant was injected into a chromatograph with a fluorescence detector set at 218 nm emission and 477 nm excitation. The isocratic elution was carried out at room temperature in reverse phase using mobile phase composed of water, acetonitrile and triethylamine. Validation of the technique included linearity tests, detection and quantification limits, intraday and interday precision, recoverability and selectivity. The method requires minimal sample pretreatment for the extraction and determination of both analytes, high precision, providing acceptable recoveries and detection limits lower than the established MRL.